PENGARUH TAKARAN PUPUK FOSFAT DAN DEFOLIASI TERHADAP KOMPONEN HASIL DAN HASIL TANAMAN JAGUNG (Zea mays L.) VARIETAS PIONEER 21 - Mardhoni, Hariyanto; Surawinata, E. Tadjudin; Purnomo, Dwi (Agroswagati : Jurnal Agronomi, 2022)
This experiment aims to determine the effect of the combination of phosphate fertilizer application and leaf pruning on the yield and yield of maize (Zea mays L.). The experiment was carried out in Mekarjaya Village, Gantar District, Indramayu Regency - West Java. The time of the study was carried out from August to November 2021. The location is located at an altitude of ± 50 m above sea level (masl), the type of soil is latosol and regosol association, including type C rain (slightly wet). The experimental method used is the experimental method with a combination randomized block design. The treatment consisted of two factors which were repeated three times. The main factor is the dose of phosphate fertilizer which consists of three levels, namely 200 kg/ha, 300 kg/ha and 400 kg/ha. While the second factor was leaf defoliation, which consisted of three levels, namely no pruning, two-leaf pruning and four-leaf pruning. The main observational data were processed using linear model statistical tests, analysis of variance, and Scott-Knot cluster further test analysis. To determine the correlation between the treatment and the yield and yield of corn, the correlation used is the Product Moment correlation coefficient. The experimental results showed: (1) The combination treatment of phosphate and defoliation doses had an effect on the weight of cobs, the number of cobs per plant, the weight of the cobs per plot, the weight of the dry shells per plot, and the weight of the dry shells per hectare, but had no effect on the length of the cobs, the diameter of the cobs, the number of rows on cobs, number of cobs per plot, weight of 100 dry shelled seeds and dry shelled weight per plant. (2) The dose of 400 kg/ha phosphate fertilizer and 2 leaf defoliation gave the highest yield of 11.43 kg per plot equivalent to 8.15 tons per hectare but not significantly different from the treatment without defoliation and 4 leaf defoliation. (3) There is a moderate correlation between the number of cobs per plot and the weight of dry shells per plot and a weak correlation to the weight of the cobs, the diameter of the cobs, the weight of the cobs, the number of rows on the cobs and the number of cobs on the plant to the weight of the dry shells per plot.